Analysis of Structures and Levels in Communication Networks - Rafinita Aditia; Neni Lefina Hektanti (Social Science Studies, 2023)
Humans have a need for communication and information. Various things are done to meet these needs. By examining the communication network that is formed in an organization or community, we can find out how human behavior as individuals in finding the information needed. Writing this article aims to review and synthesize the available literature related to the analysis of structures and levels in communication networks so that they can contribute to an understanding of the analysis of structures and levels in communication networks. The results of this research show that in this communication network, there is a structure which is an arrangement of different elements that can be identified through the pattern of communication flows in a system. By knowing the structure of this communication network, several patterns of communication and interaction can be seen, so that the roles of each individual in a group can be identified. The structure of the communication network is wheel/star, Y, chain, circle, and all channels. Meanwhile for the communication network level, namely individual communication network, relationship level, group level, and network level.